Comparison of two different biomaterials in the bone regeneration (15, 30 and 60 days) of critical defects in rats - Brassolatti,Patricia (2021)
ABSTRACT Purpose To evaluate and compare two types of different scaffolds in critical bone defects in rats. Methods Seventy male Wistar rats (280 ± 20 grams) divided into three groups: control group (CG), untreated animals; biomaterial group 1 (BG1), animals that received the scaffold implanted hydroxyapatite (HA)/poly(lactic-co-glycolic) acid (PLGA); and biomaterial group 2 (BG2), animals that received the scaffolds HA/PLGA/Bleed. The critical bone defect was induced in the medial region of the skull calotte with the aid of an 8-mm-diameter trephine drill. The biomaterial was implanted in the form of 1.5 mm thick scaffolds, and samples were collected after 15, 30 and 60 days. Non-parametric Mann-Whitney test was used, with the significance level of 5% (p ≤ 0.05). Results Histology revealed morphological and structural differences of the neoformed tissue between the experimental groups. Collagen-1 (Col-1) findings are consistent with the histological ones, in which BG2 presented the highest amount of fibers in its tissue matrix in all evaluated periods. In contrast, the results of receptor activator of nuclear factor kappa-Β ligand (Rank-L) immunoexpression were higher in BG2 in the periods of 30 and 60 days, indicating an increase of the degradation of the biomaterial and the remodeling activity of the bone. Conclusions The properties of the HA/PLGA/Bleed scaffold were superior when compared to the scaffold composed only by HA/PLGA.